2022
DOI: 10.3389/fpsyg.2022.920691
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Growth, Positive Psychology, Perceived Spousal Support, and Psychological Complications in Head and Neck Cancer: Evaluating Their Association in a Longitudinal Study

Abstract: Despite head and neck cancer (HNC) association with various negative impacts, collective evidence is accumulating regarding the positive impacts of positive psychology on cancer survivors. However, data on how positive psychology is related to the psychological complications of HNC across time are lacking. This longitudinal study examined the trends of positive psychology (e.g., posttraumatic growth [PTG], hope, and optimism), perceived spousal support, and psychological complications (e.g., depression, anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…More recently, the possibility of transformative positive changes, beyond mere recovery, namely, posttraumatic growth (PTG; Tedeschi and Calhoun, 1995, 2004, following psychological trauma has attracted considerable attention. Similar to other concepts within positive psychology such as hope, optimism, and gratitude, PTG has been recognised as a buffer for the detrimental effects of life adversities (Nik Jaafar et al, 2022;Confino et al, 2023).…”
Section: The Paradox Of the Impact Of Lifetime Traumamentioning
confidence: 98%
“…More recently, the possibility of transformative positive changes, beyond mere recovery, namely, posttraumatic growth (PTG; Tedeschi and Calhoun, 1995, 2004, following psychological trauma has attracted considerable attention. Similar to other concepts within positive psychology such as hope, optimism, and gratitude, PTG has been recognised as a buffer for the detrimental effects of life adversities (Nik Jaafar et al, 2022;Confino et al, 2023).…”
Section: The Paradox Of the Impact Of Lifetime Traumamentioning
confidence: 98%
“…With the development of positive psychology, many research results showed that significant trauma would not only bring adverse effects to individuals, but also promote them to show positive changes related to growth [ 3 ]. This phenomenon was defined as post-traumatic growth (PTG) by Tedeschi and Calhoun in 1996 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…PTG is manifested in five aspects: more meaningful interpersonal relationships, new possibilities, increased sense of personal strength, deeper appreciation for life, and richer understanding of spiritual matters ( 12 ). Previously, numerous studies have demonstrated that individuals who have experienced life-threatening events such as cancer ( 13 ), natural disasters ( 14 ) and major life changes such as divorce ( 15 ) and bereavement ( 16 ) would experience PTG. And PTG encompasses extensive benefits, varying from making meaning of the adversity ( 17 ) and turning wounds into wisdom ( 18 ) to reducing the risk of psychiatric disorders and suicide intention ( 19 , 20 ) and increasing personal development and life satisfaction ( 21 ).…”
Section: Introductionmentioning
confidence: 99%